Intensive Modes of Study and the Need to Focus on the Process of Learning in Higher Education - Lodge, Jason M.; Ashford-Rowe, Kevin (Journal of University Teaching and Learning Practice, 2024)
In the context of a constantly evolving international higher education sector, this commentary emphasises the need for consilience between basic research on learning processes and observations from intensive modes of study. Following a discussion of conflicting evidence on optimal learning time frames, we advocate for seeking alignment between classroom practices with underlying learning mechanisms. We argue for a unified understanding of effective learning beyond notions of the credit point hour or volume of learning, focusing on processes rather than mere inputs and outputs. A collaborative approach between researchers, educators, and policymakers aiming for consilience has the potential to provide practical insights and strategies to enhance student learning and success. Understanding the mechanisms beneath the impact of intensive modes of study, as outlined in this special issue, has the potential to advance the conversation about quality higher education for the 21st century.